Provision Of Assistance By Legal Advisors/Advocates To Witnesses In The Investigation Stage Examination - Tornado, Anang Shophan (International Journal of Law, Environment, and Natural Resources, 2022)
The Criminal Procedure Code only provides an opportunity for legal advisers to accompany the suspect in the Minutes of Examination with limited provisions, only to see and hear during the examination, this is regulated in Article 54 of the Criminal Procedure Code. Meanwhile, there is no regulation for witnesses in the Criminal Procedure Code. The problem in examining witnesses is when the witness being examined has the potential to become a suspect, where the concept of a witness who has the potential to become a suspect has become known as the concept of a potential suspect. So that it will be very urgent when the rights of witnesses being examined must really have their rights protected, one of the efforts to protect it is the presence of a legal adviser or advocate. The problem can be narrowed down to how witnesses who have the potential to become suspects in the investigation stage become more cooperative and "tame" towards investigators' summons to be examined, this of course needs to be made in a method that gains strong legitimacy at the norm level. In Article 27 paragraph (1) letter a Regulation of the Chief of Police Number 8 of 2009 concerning Implementation of Human Rights Principles and Standards in the Implementation of Duties of the Indonesian National Police firmly states that "every officer who conducts examination of witnesses, suspects or examinees is obliged to: a. provide an opportunity for witnesses, suspects or being investigated to contact and be accompanied by a lawyer before the examination begins.